2017
DOI: 10.1186/s12887-017-0777-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between vancomycin trough concentrations and acute kidney injury in the neonatal intensive care unit

Abstract: BackgroundVancomycin has recently gained popularity as an empiric therapy for late onset sepsis in the NICU. Changes in resistance patterns in common organisms has resulted in targeting higher trough concentrations of vancomycin. Consequently, an increase in vancomycin associated nephrotoxicity has been speculated. The objective of this study is to compare the incidence of acute kidney injury (AKI) in neonates with serum vancomycin trough concentrations less than 10 mg/L, 10–15 mg/L, or greater than 15 mg/L.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
3
28
1
1
Order By: Relevance
“…There have been studies on the risk factors for VA-AKI in the past [22][23][24]. Like previous studies, a positive correlation between VA-AKI and increasing vancomycin trough concentrations and baseline serum creatinine was found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…There have been studies on the risk factors for VA-AKI in the past [22][23][24]. Like previous studies, a positive correlation between VA-AKI and increasing vancomycin trough concentrations and baseline serum creatinine was found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…25 Previous studies have shown modest associations between vancomycin dose or trough concentrations and acute kidney injury. [26][27][28] No differences in the total vancomycin daily dose administered or in the achieved trough concentration were observed between less and more aggressive dosing strategies and toxicity in our study. However, as seen in our study and with other vancomycin nomograms targeting higher trough concentrations, risk of supratherapeutic trough concentrations are increased.…”
Section: Discussioncontrasting
confidence: 51%
“…Similarly, a retrospective study conducted by Bhargava et al concluded that there is a positive correlation between increasing vancomycin trough concentrations and increasing serum creatinine levels. Vancomycin trough concentrations above 15 mg/liter were found to be associated with a higher incidence of acute kidney injury in neonates (23). Trough concentrations lower than 10 mg/liter should also be avoided because of an increased risk of selecting for vancomycin-intermediate or vancomycin-resistant isolates (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%